2021
DOI: 10.1186/s12961-021-00788-w
|View full text |Cite
|
Sign up to set email alerts
|

Political economy analysis of universal health coverage and health financing reforms in low- and middle-income countries: the role of stakeholder engagement in the research process

Abstract: Background Progress towards universal health coverage (UHC) is an inherently political process. Political economy analysis (PEA) is gaining momentum as a tool to better understand the role of the political and economic dimensions in shaping and achieving UHC in different contexts. Despite the acknowledged importance of actors and stakeholders in political economy considerations, their role in the PEA research process beyond “study subjects” as potential cocreators of knowledge and knowledge use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…We observed that the process of policy formulation, development, and implementation in Kenya is highly in uenced by political actors and the schedule of political events. Although this is far from uncommon in the sub-Saharan context [50], we believe this poses a particularly heavy burden for the achievement of UHC in Kenya.…”
Section: Discussionmentioning
confidence: 86%
“…We observed that the process of policy formulation, development, and implementation in Kenya is highly in uenced by political actors and the schedule of political events. Although this is far from uncommon in the sub-Saharan context [50], we believe this poses a particularly heavy burden for the achievement of UHC in Kenya.…”
Section: Discussionmentioning
confidence: 86%
“…First, the goals of the cocreation should be clearly defined from the onset and understood by all stakeholders [20,22,25]. The cocreation process should also be inclusive, with trusted relationships and shared power among the stakeholders [22,24,26,27]. The discussions and decisions during cocreation should be informed by evidence [22,28,29], with the stakeholders’ experiences and perspectives as valued as the evidence provided by scientific research [24,28,30].…”
Section: Methodsmentioning
confidence: 99%
“…The PEA methodology is a structured qualitative approach examining power dynamics and economic and social forces influencing development. [23][24][25][26] The analytical approach in this study is informed by the applied political economy, which has three primary constructs: (1) problem identification, which examines the operational or developmental problem to be addressed by looking at the relationships between individuals, communities and Institutions, their motivations which are either personal, cultural, political, financial; (2a) Structural diagnosis which looks at the contextual and institutional characteristics relevant to the problem. The context examines the analysis of relevant structural features such as culture and social structures, demography, geopolitics and culture.…”
Section: Methodology Study Designmentioning
confidence: 99%